Training on traditional massage oil making from adsorbed used cooking oil at a nursing home in Brebes - Riyanta, Aldi Budi; Amananti, Wilda; Andari, Istiqomah Dwi (Journal of Community Service and Empowerment, 2024)
Used cooking oil has become a frightening specter because of the negative impacts it has caused. Used cooking oil can cause carcinogenic properties if consumed. On the other hand, the content of ginger, lemongrass and chili has been proven to produce anti-inflammatory effects. So that used cooking oil can be combined with ginger, lemongrass and chili into massage oil to be implemented in community service activities at Panti Werdha Purbo Yuwono Brebes. This community service aims to provide education and training in making massage oil from used cooking oil combined with ginger, lemongrass and chili. In addition, training is also given on proper massage for the elderly. The method used in this training is Community service activities that have been carried out have a positive impact on the participants, both the elderly and the caregivers of the orphanage. This activity has combined theoretical understanding with practical applications that form the foundation of effective massage therapy education. This study reveals that community service activity participants are provided with a real learning experience with a two-stage training approach outlined, participants not only acquire essential skills but also foster a deeper appreciation of proper massage therapy.